Technique of calligraphy (Journal of Oriental Studies, 2018)
This article explores history of the Chinese language, styles of Chinesecalligraphy. In Chinese, there are several styles, all of have some features.Different styles – changed written work in different regions of China. Theyare associated with the changes in writing means. Every student who studiesChinese must first know the history of the emergence of the Chineselanguage.